Factors associated with ball velocity and low back pain during kicking in adolescent soccer players - Tojima, M.; Takei, S.; Torii, S. (Open Access Journal of Sports Medicine, 2020)
Purpose: The factors associated with low back pain (LBP) and the relationship between LBP and ball velocity during kicking motion of adolescent soccer players remain largely unknown. This study aims to clarify the relationship between increasing ball velocity and LBP in adolescent soccer players. Participants and Methods: Adolescent soccer players were divided into two groups according to the presence and absence of LBP (LBP group, n=38 and NBP (no back pain) group, n=29, respectively). Real-time kick motion was measured using a three-dimensional motion analysis system and the angle of the lumbar spine, hip, and center of mass (COM) were calculated. Regression analysis was used to identify factors associated with ball velocity and LBP. In addition, Pearson`s correlation coefficients were determined between the angle of the lumbar spine and hip, and ball velocity and position of COM in the extracted phase from regression analysis. Results: The major factor associated with increasing ball velocity was the rotation angle of both hips (Adjusted R2=0.244) and vertical position of COM during kicking (Adjusted R2=0.262). Furthermore, the factors associated with LBP were the flexion angle of kick-side hip (OR=1.126) and abduction angle of both hips (kick-side OR=1.124; support-side OR=0.872). The factors for ball velocity and LBP were related to the maximum hip extension phase. In the hip extension phase of kicking, compared with the NBP group, the LBP group showed lesser extension and external rotation of the kick-side hip angle. In the hip flexion phase of kicking, the ball velocity was correlated with vertical (r=0.56)/anterior (r=0.46) position of COM in the NBP group. Conclusion: To compensate for this restricted hip motion, the LBP group could extend and rotate their lumbar spine, which may likely cause stress to this region.